Trends in thyroid cancer incidence and mortality in Portugal. Issue 2 (March 2017) - Raposo, Luís; Morais, Samantha; Oliveira, Maria J.; Marques, Ana P.; José Bento, Maria; Lunet, Nuno
Abstract : The objective was to quantify thyroid cancer incidence and mortality trends in Portugal. The number of thyroid cancer cases and incidence rates were retrieved from the Regional Cancer Registries for the period 1989–2011. The number of deaths and mortality rates were obtained from the WHO cancer mortality database (1988–2003 and 2007–2012) and Statistics Portugal (2004–2006; 1988–2012 by region). Joinpoint regression of the standardized incidence and mortality rates was performed. A significant, rapid and continued increase in incidence was observed for both sexes in each of the Regional Cancer Registries, with annual per cent changes (APCs) ranging between 2 and 9. Incidence in Portuguese women is higher than estimates for the world and Europe. Mortality decreased for women (APC: −1.5), with the greatest decrease in the North, and increased marginally for men (APC: +0.2), with a greater increase in the South. The significant increases in incidence in Portugal are predominantly because of the increase in incidence among women from the North. These trends, combined with an overall low mortality and high 5-year relative survival, raise concerns on the extent to which overdiagnosis may be taking place. Further research is needed, quantifying the importance of the most likely determinants of these trends as well as the extent and potentially deleterious effects of overdiagnosis and overtreatment in the Portuguese setting.